1989
DOI: 10.1002/1097-4679(198905)45:3<423::aid-jclp2270450311>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Screening for learning disabilities: A neuropsychological approach

Abstract: The ability of the Trail Making Test (TMT) and Tactual Performance Test (TPT) to discriminate between learning‐disabled and normal children was examined. Twenty children aged 9 to 14 years who recently had been classified as learning disabled and 20 matched controls were administered individually the TPT, TMT, and two experimental forms of the TMT (parts X and Y). The data from the two groups were analyzed with a discriminant analysis. An overall accuracy rate of 82.5% was obtained when the measures were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
5

Year Published

1993
1993
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 5 publications
0
5
0
5
Order By: Relevance
“…The TMT is a widely used tool for assessing executive and other prefrontal functions (Sellers & Nadler, 1992) in adults and has also been used with children of varying ages (Davis, Adams, Gates, & Cheramie, 1989). The task consists of three trials (numbers, letters, and a combination of numbers and letters) of connecting a series of dots in ascending order with a pencil.…”
Section: Methodsmentioning
confidence: 99%
“…The TMT is a widely used tool for assessing executive and other prefrontal functions (Sellers & Nadler, 1992) in adults and has also been used with children of varying ages (Davis, Adams, Gates, & Cheramie, 1989). The task consists of three trials (numbers, letters, and a combination of numbers and letters) of connecting a series of dots in ascending order with a pencil.…”
Section: Methodsmentioning
confidence: 99%
“…The final task administered to children at T4 was an adapted version of the Trial-Making Task (TMT ; Reitan, 1971) which was given to assess children's executive functioning. The TMT is a widely used tool for assessing executive and other prefrontal functions (Sellers & Nadler, 1992) in adults and has also been used with children of varying ages (Davis, Adams, Gates, & Cheramie, 1989). The task consists of three trials (numbers, letters, and a combination of numbers and letters) of connecting a series of dots in ascending order with a pencil.…”
Section: Methodsmentioning
confidence: 99%
“…Aiming to evaluate speech initiation and regulation, Mergler et al [1994] used the Digit Naming Test [Davis et al, 1987] and found that exposed workers were significantly slower on the second trial of this test. The Controlled Oral Word Association Test [Lezak, 1995] assesses verbal fluency and was administered in three studies Bowler et al, 2006Bowler et al, , 2007 with no significant observations.…”
Section: Occupational Studies: Cognitive Functionsmentioning
confidence: 99%